Implementation of Domain Name System (DNS) Filter for Blocking Online Gambling Domains based on Raspberry Pi: Rekayasa Keamanan Siber - umarfaruq; Heri Setiawan; Yohanes Dwi Cahyono (Pustaka Poltekad, 2026)
The increased internet access in military education environments, including at the Poltekad Kodiklatad, has also opened up opportunities for abuse, such as access to online gambling, which has the potential to cause economic, social, and mental impacts, as well as information security risks through social engineering schemes. Data from the Ministry of Communication and Information of the Republic of Indonesia (2023) shows that thousands of online gambling domains are blocked, but domain fluxing practices cause the block list to quickly become outdated. On the other hand, a report from the National Cyber ​​and Crypto Agency (2023) noted an increase in cyberattacks against defense institutions through the exploitation of user vulnerabilities. This study aims to develop and test a Raspberry Pi 4-based DNS Filtering system as a low-cost network security solution and zero-touch enforcement in the Poltekad environment. The method used is Research and Development (R&D) with a single-group pretest-posttest experimental design to measure the system's effectiveness before and after implementation. The four evaluation parameters include the effectiveness of blocking gambling domains, the false positive rate, the impact of DNS latency compared to Google DNS 8.8.8.8, and resistance to bypass (DoH, direct IP access, and VPN). The implementation results show that the system is capable of plug-and-play operation via Pi-hole as a transparent gateway at a cost of Rp2,150,000, lower than proprietary solutions. This research produces a blueprint for implementing open-source DNS Filtering that is effective, efficient, and replicable as a model for securing military unit networks in accordance with the policy of utilizing open technology within the Indonesian Army.